Program Kemahasiswaan Dalam Pemenuhan Indikator Kinerja Utama (IKU) Perguruan Tinggi – Best Practice - Libianko Sianturi; Sindak Hutauruk; Mula Sigiro; Hamonangan Siallagan; Jamser Simanjuntak (Jurnal Visi Pengabdian Kepada Masyarakat, 2023)
Higher education KPI consist of eight indicators that measure the quality of graduates, lecturers, and curriculum. Based on the BK2PTKI invitation letter No. 07/BK2-PTKI/X/2022 dated 18 October 2022, the author was invited to attend as speakers with the topic: "Student Affairs Program in Fulfillment of Higher Education Key Performance Indicators (KPI) - Best Practice".On this occasion, we describe several important matters regarding the role of student affairs in fulfilling KPI, including: implementation of MBKM, BELMAWA and PUSPRESNAS programs, development and revitalization of student body, increasing cooperation with foreign universities and increasing cooperation with domestic universities.